The role of zirconia in cobaltosic oxide catalysts for low-temperature CO oxidation. Issue 112 (22nd November 2016) - Du, Fan; Wu, Guisheng; Mao, Dongsen; Lu, Guanzhong
Abstract : A series of Co3 O4 /ZrO2 catalysts for low-temperature CO oxidation was prepared, and then characterized by low-temperature N2 adsorption/desorption, XRD, TEM, XPS, UV-vis, CO-TPR, CO adsorption and CO2 desorption. Abstract : A series of Co3 O4 /ZrO2 catalysts for low-temperature CO oxidation was prepared with different ZrO2 loadings and different preparation methods, and then characterized by low-temperature N2 adsorption/desorption, XRD, TEM, XPS, UV-vis, CO-TPR, CO adsorption and CO2 desorption. The results show that ZrO2 not only increases the specific area and decreases the crystal size of Co3 O4 in CZ-c-20 and CZ-f-20, but also promotes production of Co 2+ and –O −, which shows the high catalytic activity for CO oxidation. The facile decomposition of carbonate and the high redox properties over ZrO2 promote the catalytic stability for CO oxidation.